(untitled) (International Journal of Nursing Education, 2020)
Background: Workplace trust is considered one of the most important factors for organizational success;trust can be achieved by authentic leaders when they are transparent and consistent toward their followers. Authentic leaders could make suitable work environment, where bullying doesn’t occur. Aim: Examine workplace trust and authentic leadership as predictors of work-related bullying among staff nurses. This study was carried out at Zagazig University hospitals, Egypt. For this research, a descriptive research design was used. Method: A stratified random sample of 403 staff nurses were selected from the aforementioned setting. Three tools were utilized for data collection: Authentic leadership questionnaire, workplace trust survey and negative acts questionnaire. Results: Proved highly statistically significant positive correlation between workplace trust and authentic leadership (r=0.853, p <0.001). Otherwise, workplace trust and authentic leadership were negatively and significantly correlated with workplace bullying (r=-0.473 & -0.519, respectively, p <0.001). Conclusion: authentic leadership and workplace trust are negative predictors of work-related bullying. Therefore, it is recommended to develop and implement authentic leadership practices a strategy for eliminating work-related bullying.